(untitled) (Damascus University Journal for engineering sciences, 2025)
Due to the scarcity of potable water, and the difficulty of obtaining it from known natural sources ,it is natural to search for other ways to solve this shortage by extracting salt from sea water and benefiting from ground water in order to obtain drinkable water. Solar distillation is a solution proposed to solve the problem of the shortage of potable water. In this research, the mathematical model of the proposed system ( a box solar still+ a solar pond) was studied for a city in the Damascus countryside because it contains calcareous water, and it is productivity was compared with a simple, tow- inclined box still with abase area of (1m2) according to the climatic conditions of a city in Damascus countryside, at sufficient amounts of water. (15 liter/m2day) (20 liter/m2day) (50 liter/m2day) and (70 liter/m2day), based on the Excel program using the repetition method. It was found that the best distillation yield was obtained with an amount of water (70 liter/m2day) where the distillation yield value reached (70%).